BRANDING AND CRAFT TECHNOLOGIES OF AGRICULTURAL ENTERPRISES: A STRATEGIC ASPECT - KRASNORUTSKYY, Oleksiy (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In modern conditions, opening a business based on the principles of craft technologies is relevant for agricultural producers of Ukraine, because it allows to reduce the risks of security issues and unemployment. Economic processes in the country are changing very quickly, customer requests for unique products and quality are undergoing transformations. Therefore, managing the brand of craft producers will provide an opportunity to find effective ways to optimize costs and efforts to enter new local markets, including foreign ones. The purpose of the study is to determine the current state and strategic aspects of the development of branding based on craft technologies of agricultural enterprises. The existence of an inseparable synergistic effect from a positive brand of a craft product of an agricultural enterprise for both the business entity itself and the consumer is substantiated. This can be traced through the corresponding economic and social result (profit, expenses, satisfaction of needs, emotions). Particular attention is paid to such a feature of a craft product as the personal participation of the owner in its production. The image of such a key person will determine the direction of branding and the perception of its development. The situation that has developed in Ukraine with the organization of craft productions has been analyzed and the most developed types of activities in the agricultural sector have been identified (bakery and confectionery, alcoholic beverages, cheese and dairy products, meat, honey products and canned goods). The main difficulties are related to unsatisfactory marketing, financial difficulties, uncertainty due to military aggression. The strategic aspects of agribusiness that should be planned by the manager in the context of the introduction of craft technologies are substantiated and analyzed: (strategy and tactics of a new type of activity based on craft technology; choosing the location of an agricultural enterprise; choosing suppliers; sources of financing and assessing the impact of craft product development on the image of an agricultural enterprise).